Quality Analysis of Pressure Measurement Automatic Sphygmomanometer and Non-automatic Sphygmomanometer - Yeni Pertiwi; Nur Hadziqoh; Romi Mulyadi; Nabila Noria Putri; Rizki Eka Putra (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
Hypertension is the fifth leading cause of death in Indonesia. Hypertension occurs because the blood vessels are continuously experiencing high pressure. Medical device that supports doctors and other health workers in diagnosing hypertension is sphygmomanometer. Sphygmomanometer is an instrument for measuring blood pressure. Accuracy of blood pressure measurement is very important in diagnosing hypertension. An Error in measuring blood pressure will be fatal for patients, health workers, and health facilities. So that this study aims to analyze the quality of automatic and non-automatic sphygmomanometer. This research method is in form of quantitative research based on experiments. The data was taken by using direct measurements. Measurements were carried out by using the 2018 Ministry of Health work method. Quality assessment of the sphygmomanometer was taken based on the results of sphygmomanometer calibration analysis. Automatic sphygmomanometer with the OMRON brand got score 95 and the non-automatic sphygmomanometer with the ABN brand got score 97.3. The results of the analysis showed that both tools had high accuracy of pressure measurement and were within tolerance limits. So it can be concluded that both tools are feasible to use.